Developing Peer Mediated Interventions for Secondary Students with Emotional and Behavioral Disorders - Feeney, Danielle (Journal of the American Academy of Special Education Professionals, 2018)
Social skills training has become a major focus for improving the lives of individuals with disabilities. Students with emotional and behavioral disorders often lack the social skills necessary to build and maintain positive relationships with others and require individualized training to appropriately engage across all settings. Despite the growth of research in this topic, there is little known about the efficacy of peer-mediated interventions for high school students who have emotional and behavioral disorders. Peer mediators act as models and supports for students with emotional and behavioral disorders by providing cues, feedback, and praise. This paper suggests ways that classroom teachers can develop peer-mediated interventions at a secondary level.